Improving the accuracy of calculating the speed of movement at the time of an accident in collisions with incomplete overlap of a part of the car - E. V. Golov (Вестник СибАДИ, 2021)
Introduction. Driving at a speed exceeding the permitted and average speed of traffic flow often leads to a collision of vehicles with other road users or with elements of the arrangement of highways. As a result, it is necessary to establish whether the fact of this violation of the traffic rules, which led to the occurrence of an emergency-dangerous road traffic situation. The methods used to calculate the speed of vehicles based on the resulting deformations are quite accurate, but this fact is true in conditions of complete overlap (impact across the entire width of the front, rear or side parts of the body). But there is a scientific task of developing a methodology according to which an expert or investigator will be able to calculate the average statistical value of measuring the depth of deformation of a vehicle for a specific road traffic situation.Materials and methods. The paper proposes a method for evaluating the possibility of using the data available to the expert for calculation by introducing the coefficient of variation of the depth of penetration. With the help of the coefficient of variation, the specialist has a tool for selecting and ignoring individual measurements of the depth of penetration, depending on the degree of overlap and on the ‘spread’ of the deformation values.Conclusions. After studying a number of collisions with incomplete overlap and excluding the ‘extra’ values of penetration, the speed equivalent to the energy cost for the development of residual deformations and errors (the difference between the true collision speed and the established one without taking into account the ‘falling out’ values of deformations) was calculated and it was found that the use of the algorithm taking into account the coefficient of variation led to sufficiently accurate calculation results.Discussions. The proposed methodology regulates the use of the coefficient of variation as a criterion for the admissibility of the use of source data to determine the quality of the final result of the calculation. This mathematical device is applicable to all collisions, but is especially relevant when studying collisions with incomplete overlap of any part of the car body.